Generation of KS-58 as the first K-Ras(G12D)-inhibitory peptide presenting anti-cancer activity in vivo - Sakamoto, Kotaro; Masutani, Teruaki; Hirokawa, Takatsugu (Scientific Reports, 2020)
Ras mutations (e.g., occur in K-Ras, N-Ras, and H-Ras) are one of the most desirable and promising drug targets in chemotherapy treatments for cancer. However, there are still no approved drugs directly targeting mutated Ras. In 2017, an artificial cyclic peptide, KRpep-2d, was discovered as the first selective inhibitor of K-Ras(G12D), the most frequent K-Ras mutation. Here, we report the generation of KS-58, a KRpep-2d derivative that is identified as a bicyclic peptide and possess unnatural amino acid structures. Our in vitro data and molecular dynamics simulations suggest that KS-58 enters cells and blocks intracellular Ras–effector protein interactions. KS-58 selectively binds to K-Ras(G12D) and suppresses the in vitro proliferation of the human lung cancer cell line A427 and the human pancreatic cancer cell line PANC-1, both of which express K-Ras(G12D). Moreover, KS-58 exhibits anti-cancer activity when given as an intravenous injection to mice with subcutaneous or orthotropic PANC-1 cell xenografts. The anti-cancer activity is further improved by combination with gemcitabine. To the best of our knowledge, this is the first report of K-Ras(G12D)-selective inhibitory peptide presenting in vivo anti-cancer activity. KS-58 is an attractive lead molecule for the development of novel cancer drugs that target K-Ras(G12D).